2017
DOI: 10.1007/s13402-017-0318-8
|View full text |Cite
|
Sign up to set email alerts
|

Silymarin and its active component silibinin act as novel therapeutic alternatives for salivary gland cancer by targeting the ERK1/2-Bim signaling cascade

Abstract: Taken together, we conclude that ERK1/2 signaling pathway inhibition by silymarin and silibinin increases the expression of the pro-apoptotic Bcl-2 family member Bim which, subsequently, induces mitochondria-mediated apoptosis in salivary gland cancer-derived cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 51 publications
3
12
0
Order By: Relevance
“…Silibinin induced apoptosis in human choriocarcinoma cells [ 33 ]. The anti-cancer effects of SLM and silibinin on salivary gland cancer have also been reported by Choi et al (2017) [ 34 ]. Chen et al (2018) showed that taxifolin suppressed the proliferation of human osteosarcoma cells [ 35 ].…”
Section: Discussionsupporting
confidence: 57%
“…Silibinin induced apoptosis in human choriocarcinoma cells [ 33 ]. The anti-cancer effects of SLM and silibinin on salivary gland cancer have also been reported by Choi et al (2017) [ 34 ]. Chen et al (2018) showed that taxifolin suppressed the proliferation of human osteosarcoma cells [ 35 ].…”
Section: Discussionsupporting
confidence: 57%
“…Our research group recently found naturally-derived chemicals such as silymarin, caffeic acid phenethyl ester, and oridonin have anticancer efficacies by inducing apoptosis of HNCCs. (2123) Fisetin is also naturally derived compound that can be easily synthesized and has no toxicity to normal cells. (24) First, we demonstrated that fisetin reduced cell viability and induced apoptosis in four different HNCCs (HSC3, MC3, Ca9.22, and HN22).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, silibinin is also found to display various biological activities including anti-oxidative, anti-proliferative, anti-bacterial, anti-fungal, neuro-protective, anti-leishmanial, anti-osteoclastic and anti-metastatic activities [310][311][312][313][314][315][316][317]. Previous studies have reported that silibinin exerts remarkable effects in numerous cancers such as renal, hepatocellular and pancreatic carcinoma, bladder, breast, colorectal, ovarian, lung, salivary gland, prostate and gastric cancers, through the induction of apoptosis, inhibition of tumor growth, metastasis and angiogenesis [318][319][320][321][322][323][324][325][326][327][328].…”
Section: Silibininmentioning
confidence: 99%